Health and safety risks behavior among local and international tourists at Borobudur Temple before COVID-19 pandemic - Zahroh Shaluhiyah; Antono Suryoputro; Delita Septialti (Intelektual Pustaka Media Utama, 2023)
Tourists are vulnerable to certain diseases and health-related issues, including experiencing danger during their visit to a destination. This study aims to compare the health and safety behavior of local and foreign tourists during their visit to Borobudur Temple, Indonesia from September to November 2019. Additionally, it was carried out quantitatively with a cross-sectional approach. The sample consisted of 200 foreign and 200 local tourists visiting Borobudur Temple; they were selected using convenient sampling. The data were analyzed using the frequency distribution and the Chi-square test. The results showed that health risks related to food and beverage hygiene were the most experienced by foreign tourists (p-value 0.030), and solar radiation effects were experienced by both foreign and local tourists (p-value 0.006). Tourists' knowledge to prevent health and safety risks was categorized as moderately adequate, and foreign tourists have more understanding than their local counterparts. This study reported no difference in health and safety behaviors between foreign and local tourists. It was suggested that tourism managers should provide information to the visitors concerning health and safety risks prevention by delivering leaflets, booklets, and brochures to minimize danger, sunburn, and food as well as beverage-related diseases.